Settlement Of Marine Boring Bivalve Larvae On Wood Soaked Horizontally And Vertically In Pelabuhan Ratu Bay, West Java - Fredinan Yulianda (Masyarakat Moluska Indonesia, 2019)
Pieces of red meranti wood (Shorea leprosula) were soaked in horizontal and vertical positions in sea water for 9 weeks. Two species of bivalves settled on the wood: Bankia campanellata (Moll & Roch) and Martesia striata (Linné). Average densities of settling larvae were 125 ind. 100 cm-2 on horizontal wood, and 95 ind. 100 cm-2 on vertical wood, indicating a tendency to settle on the top side of the wood. The number of larvae settling on wood immersed at the surface was not significantly different from wood at 1.25 m depth.